Mechanism of the blood-brain barrier modulation by cadherin peptides - Elinaz Farokhi; Ahmed L. Alaofi; Vivitri D. Prasasty; Filia Stephanie; Marlyn D. Laksitorini; Krzysztof Kuczera; Teruna J. Siahaan (Exploration of Drug Science)
Aim: This study was aimed at finding the binding site on the human E-cadherin for Ala-Asp-Thr Cyclic 5 (ADTC5), ADTC7, and ADTC9 peptides as blood-brain barrier modulator (BBBM) for determining their mechanism of action in modulating the blood-brain barrier (BBB). Methods: ADTC7 and ADTC9 were derivatives of ADTC5 where the Val6 residue in ADTC5 was replaced by Glu6 and Tyr6 residues, respectively. The binding properties of ADTC5, ADTC7, and ADTC9 to the extracellular-1 (EC1) domain of E-cadherin were evaluated using chemical shift perturbation (CSP) method in the two dimensional (2D) 1H-15N-heteronuclear single quantum coherence (HSQC) nuclear magnetic resonance (NMR) spectroscopy. Molecular docking experiments were used to determine the binding sites of these peptides to the EC1 domain of E-cadherin. Results: This study indicates that ADTC5 has the highest binding affinity to the EC1 domain of E-cadherin compared to ADTC7 and ADTC9, suggesting the importance of the Val6 residue as shown in our previous in vitro study. All three peptides have a similar binding site at the hydrophobic binding pocket where the domain swapping occurs. ADTC5 has a higher overlapping binding site with ADTC7 than that of ADTC9. Binding of ADTC5 on the EC1 domain influences the conformation of the EC1 C-terminal tail. Conclusions: These peptides bind the domain swapping region of the EC1 domain to inhibit the trans-cadherin interaction that creates intercellular junction modulation to increase the BBB paracellular porosity.